Immature to Total Neutrophil (I/T) Ratio sebagai penunjang Diagnosis Sepsis Neonatorum - Bastiana, Bastiana; Aryati, Aryati; Iriani, Yulia (Indonesian Association of Clinical Pathologist and Medical laboratory, 2010)
Early diagnosis of neonatal sepsis plays an important role in the management of patients. Blood culture, currently used as thegold standard, has several limitations such as time consuming and low positive rate. For this reason, a rapid and accurate diagnosticmethod is required. Manual differential count is a practical, inexpensive method and can support the diagnosis of bacterial infections.A shift to the left in differential white count with a raised immature neutrophil count has been documented in patients with bacterialinfections. This led to the use of I/T ratio as a indicator towards bacterial infections. The aim of this study is to obtain the diagnosticvalue of I/T ratio in diagnosing neonatal sepsis. The study was a prospective and cross-sectional. The subjects were enrolled consecutively,consisting of newborn babies (from birth to 30-days old) admitted to the Neonatal Intensive Care Unit (NICU) of the Dr. SoetomoHospital, Surabaya. Forty and three samples, consisting of 13 sepsis samples and 30 nonsepsis as controls samples were examined. I/Tratio are a ratio between immature neutrophils against total neutrophils in blood smear preparation. For the determination of the whitecell differential count, a total of 100 white cells (granulocytes) were counted. I/T ratio > 0.2 showed an abnormality that suggestaninfection process occur. Blood smear evaluations were done by three (3) independent observers. The result from three (3) observerswere as follows: sensitivity and specificity of I/T ratio in the diagnosis of neonatal sepsis were 69.2%, 92.3%, 61.5% and 50%, 50%,63.3%, respectively. Positive and negative predictive values were 37.50%, 44.44%, 42.10% and 78.94%, 93.75%, 79.16%, respectively.According to Cochran test there was no difference found between the 3 observers (p = 0.086). However, using Kappa test no agreementbetween I/T ratio and sepsis (p = 0.051) differences were found. from this study so far, the value in the diagnosis of neonatal sepsis theI/T ratio showed a low diagnostic.